Antimicrobial Metabolites Produced by Penicillium mallochii CCH01 Isolated From the Gut of Ectropis oblique, Cultivated in the Presence of a Histone Deacetylase Inhibitor - Zhang, Shuxiang; Fang, Han; Yin, Caiping; Wei, Chaoling; Hu, Jingwei; Zhang, Yinglao (Frontiers in Microbiology, 2019)
Abstract Three chemical epigenetic modifiers (5-zazcytidine，nicotinamide, suberoylanilide hydroxamic acid) were applied to induce the metabolites of Penicillium mallochii CCH01, a fungus isolated from the gut of Ectropis oblique. Metabolite profiles of P. mallochii CCH01 was obviously changed by suberoylanilide hydroxamic acid (SAHA) treatment. Four metabolites (1-4), including 2 new natural sclerotioramine derivatives, isochromophilone XIV (1), isochromophilone XV(2) and 2 known compounds, sclerotioramine (3) and (+)-sclerotiorin (4), were isolated and purified from P. mallochii CCH01 treated with SAHA. Their structures were determined by spectroscopic analyses. Anti-phytopathogenic activities of the isolated compounds 1-4 were investigated under laboratory conditions, and compound 4 showed broad and important inhibition activities against Curvularia lunata (IC50 = 2.1 μg/mL), C. clavata (IC50 = 21.0 μg/mL), Fusarium oxysporum f. sp. Mornordica (IC50 = 40.4 μg/mL) and Botryosphaeria dothidea (IC50 = 27.8 μg/mL), which were comparable to those of referenced cycloheximide, with IC50 values of 0.3, 5.0, 12.4 and 15.3 μg/mL, respectively. Ingredients 2 and 3 showed selective and potent activities against Colletotrichum graminicola with the IC50 values of 29.9 and 9.7 μg/mL, respectively. Furthermore, the antibacterial bioassays showed that compounds 3 and 4 exhibited strong inhibition activities against Bacillus subtilis, with disc diameters of zone of inhibition (ZOI) of 9.1mm and 9.1mm respectively, which were a bit weaker than that of referenced gentamycin with ZOI of 10.8 mm. Additionally, the new metabolite 1 showed a promising activity against Canidia albicans (ZOI =10.5 mm), comparable to that of positive amphotericin B with ZOI of 23.2 mm. The present results suggest that chemical epigenetic modifier induction was a promising approach to obtaining antimicrobial metabolites encoded by silent biosynthetic of P. mallochii.